Afriforum Jeug members’ reaction to the Afrikaans Must Fall movement : an application of Earl Hopper’s theory of the traumatogenic process - Liccardo, Sabrina (University of Pretoria, 2022)
Mini Dissertation (MA (Research Psychology))--University of Pretoria, 2022.